Old and new challenges in the wine business: What lies ahead for wine economics and policy - Nicola Marinelli (Wine Economics and Policy, 2022)
The wine sector, as all the other businesses, is facing the effects of the recent global pandemic and of the energy price crisis, but at the same time the research has not finished dealing with old/new challenges in the field of sustainability and innovation. And probably never will, as these issues represent an underlying constant in the debate. As the wine world continues to change, our Journal changes: eleven years after the publication of the first Issue, it is time to take stock of the situation and discuss what lies ahead.
Keywords: 330; wine; business; research; sustainability; innovation